2021
DOI: 10.1021/acssuschemeng.1c03549
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Carbon Fiber Networks by Design from Renewables for Electrochemical Applications

Abstract: With the explosion of global demands for electrified mobility systems and a surge in rural energy transport mechanisms augmented by the scarcity of key metals, carbon by design has become a transformational pathway to fill the gap as an energy material of choice. The development of functional carbon from renewables with outstanding electrostatic double-layer capacitance is still in its infancy, as there is a significant gap in understanding the relationship between the tunable structure and properties of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The carbon content and molecular weight (MW) of the lignins can affect the final carbon yield. In one of our previous studies, Wei et al [ 18 ] reported that HL and SL had considerably higher overall ratios of aliphatic to aromatic carbons than KL and LB. KL and HL have similar MW and showed similar carbon yield [ 18 ], which is in conformity to the results discussed here.…”
Section: Resultsmentioning
confidence: 97%
“…The carbon content and molecular weight (MW) of the lignins can affect the final carbon yield. In one of our previous studies, Wei et al [ 18 ] reported that HL and SL had considerably higher overall ratios of aliphatic to aromatic carbons than KL and LB. KL and HL have similar MW and showed similar carbon yield [ 18 ], which is in conformity to the results discussed here.…”
Section: Resultsmentioning
confidence: 97%
“…6,7 Nevertheless, the manufacture of flexible electrodes from AC powders generally requires flexible collectors (e.g., metal mesh, 8 graphite paper, 9 carbon paper 10 ) loading inactive polymer binders 11 (e.g., PTFE, PVDF) and conducting agents 12 (e.g., carbon black), which reduce the energy density but increase the cost of FSSCs. 13 To date, a variety of carbon-based freestanding electrodes have been developed from self-supported networks of carbon nanotubes (CNTs), 14 graphene papers 15 and carbon nanofibers 16 for their excellent mechanical robustness, high conductivity and chemical stability. 17,18 Nevertheless, their large-scale application in FSSCs is hindered by high expense and low specific capacitance.…”
mentioning
confidence: 99%
“…, carbon black), which reduce the energy density but increase the cost of FSSCs. 13 To date, a variety of carbon-based freestanding electrodes have been developed from self-supported networks of carbon nanotubes (CNTs), 14 graphene papers 15 and carbon nanofibers 16 for their excellent mechanical robustness, high conductivity and chemical stability. 17,18 Nevertheless, their large-scale application in FSSCs is hindered by high expense and low specific capacitance 19…”
mentioning
confidence: 99%